Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Bagian Bongkar Muat Barang Di Terminal Peti Kemas Cabang Panjang - Nelson NELSON (Universitas Bandar Lampung (UBL), 2012)
Container unit as one part of the PT. Pelabuhan Indonesia II (Persero) to manage the loading and unloading of goods in containers. Therefore, employee training is needed to improve employee performance. The problem faced is: not all oprator cranes have the same speed in performing activities of unloading and reloading of containers, the understanding and control of container cranes loading and unloading equipment varying, frequency of training is less likely to cause a lack of understanding of the use of total padap terh loading and unloading equipment, yan and low employee performance. The formulation of the problem is whether the effect of job training on the performance of employees in the loading and unloading of goods in Container Terminal cabang Panjang. The purpose of the study was to determine pengharuh job training on the performance of employees in the loading and unloading of goods in Container Terminal cabang Panjang. From a qualitative analysis of the results obtained: 40% for job training job training of employees expressed well, 40% moderate, and 20% lower, 36% for employee performance expressed well, 44% moderate, 20% lower. Based on the results of quantitative analysis with a linear regression model as a regression equation: Y = 7.666 + 0,622X which shows that the constant 7.666 means if the job training = 0, then the employee's performance is positive at 7.666. Variable regression coefficient of 0.622 job training job training means that if = 1, then the employee's performance will be increased by 0.622. The coefficient of determination of 37.1% means that job training has contributed as much as 37.1% on employee performance and by 62.9% influenced by other factors. Based on t-test results obtained by t-test 3.684> 2.069 t-table, then Ho is rejected and Ha accepted, which means job training effect on employee performance. It can be concluded that the hypothesis that job training have a significant effect on the performance of employees in the loading and unloading of goods in Container Terminal cabang Panjang acceptable.